Primary Productivity, Compartment Transfers and System Transfer Functions in Chrysopogon Fulvus Grasslands - Shanker, Vinod; Velayudhan, K C; Kanodia, K C (Annals of Arid Zone, 2016)
Chrysopogon futvus grasslands are major constituents of the Sehima - Dicheanthium cover. The present study is a prt of the overall study of its production ecology and deals with herbage dynamics of the primary producers. The productive structure of the community exhibited market stratification in vertical distribution of the foliage and an overall dominance of C. fulvus at all the heights. The seasonal variation of abovergound standing crop nearly parallels that of Sehima- Heteropogon and other grasslands elswere in India where it is observed to correspond with the seasnal distribution of rainfall. The seasonal variation in the litter production corresponds to the period wherein the standing dead biomass increases the litter production through shattering, leaf fall and senescence. The below ground biomass showed increase just after monsoon and spring growths of the aboveground standing crop. Compartment transfers and system transfer functions give an overall picture of belowground directed orientation of ecosystem functioning in C. fulvus grasslands.